2008
DOI: 10.1080/13693780802060899
|View full text |Cite
|
Sign up to set email alerts
|

Yeast diversity in the oral microbiota of subjects with periodontitis:Candida albicansandCandida dubliniensiscolonize the periodontal pockets

Abstract: The term periodontitis encompasses several polymicrobial infectious diseases, of multifactorial etiology, with chronic and aggressive forms. In spite of the etiopathogenic differences between these two forms of the disease, few studies have analyzed the subgingival colonization by yeast. The objective of this investigation was to analyze the composition of the yeast microbiota present in the mucosa and subgingival sites of healthy individuals and patients with aggressive and chronic periodontitis. For this, sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
111
3
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 44 publications
11
111
3
9
Order By: Relevance
“…This study determined that C. parapsilsosis sensu stricto is more likely to be recovered from oral cavities under pathological conditions, which agrees with a Chilean study published in (2008) [10], where a lower yeast prevalence is observed, evidenced in a lower count of colony-forming units (CFU/ml) of Candida species among periodontally healthy subjects when compared to individuals with periodontal disease; the difference being statistically significant. Similar results were reported by Canabarro A et al in (2013) [50], since the results of their investigation showed that patients with severe chronic periodontitis are significantly more colonized, at the level of subgingival niches, by several species of Candida especially Candida albicans with respect to subjects periodontally healthy.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This study determined that C. parapsilsosis sensu stricto is more likely to be recovered from oral cavities under pathological conditions, which agrees with a Chilean study published in (2008) [10], where a lower yeast prevalence is observed, evidenced in a lower count of colony-forming units (CFU/ml) of Candida species among periodontally healthy subjects when compared to individuals with periodontal disease; the difference being statistically significant. Similar results were reported by Canabarro A et al in (2013) [50], since the results of their investigation showed that patients with severe chronic periodontitis are significantly more colonized, at the level of subgingival niches, by several species of Candida especially Candida albicans with respect to subjects periodontally healthy.…”
Section: Discussionsupporting
confidence: 80%
“…Other species less frequently isolated, which have been recovered from periodontal environments and the oral mucosa, are the following: C. parapsilosis, C. dubliniensis, C. tropicalis and C. guilliermondi, among others [9][10][11][12][13][14]. However, over the last ten years, some studies have found an increasein the non-albicans Candida (NAC) recovery frequency in oral mucosa: from 10 % in 1996 [1] to 15.0% [7] in 2010, 15.4 % in 2011 [8], and 25.0% in 2017 [14] in the case of C. parapsilosis at the level of healthy Citation: María L Rodríguez, Alcira C Rosa, Jennifer G Rodríguez, María L Nastri and Virginia M Jewtuchowicz (2018) The Oral Cavity: A Reservoir that Favors Colonization and Selection of Candida parapsilosis sensu stricto Strains with High Pathogen Potential Under Conditions of Gingivalperiodontal Disease.…”
Section: Introductionmentioning
confidence: 99%
“…2,27 The yeast C. albicans lives in a state of commensalism in the oral cavity but is also an important opportunistic pathogen that can cause infections varying from harmless newborn thrush to severe deep mucocutaneous candidiasis or even sepsis in patients with a local or systemic compromised immune response or in patients who take antibiotics. 28 " 30 Our investigation has revealed that the killing efficacy of chlorhexidine against S. sanguinis was weaker than that of mouth rinses containing octenidine or polyhexamethylene biguanide (Figure 1). This finding is in accordance with that of Decker et al 31 In ascending order, the following mouth rinses were found to be the most effective against S. mutans: those containing chlorhexidine, those containing polyhexamethylene biguanide, and those containing octenidine.…”
Section: Discussionmentioning
confidence: 99%
“…Hyphae provide structural integrity to biofilms (Finkel and Mitchell, 2011;Banerjee et al, 2013). C. albicans has been found in periodontal pockets in both the chronic and aggressive forms of periodontitis (Urzua et al, 2008).…”
Section: Introductionmentioning
confidence: 99%